PENGARUH PENERAPAN STRUKTUR PENGENDALIAN INTERN TERHADAP EFISIENSI PENYALURAN KREDIT PADA LEMBAGA PERKREDITAN DESA (LPD) DI KECAMATAN ABIANSEMAL - Ni Putu Puspita Dewi; I Putu Nuratama (UNHI Press, 2022)
This study aims to prove empirically the effect of internal control elements on the efficiency of credit distribution in LPD Abiansemal District. The data used in this study is primary data in the form of questionnaire answers. The population used in this study were all LPD employees in Abiansemal District as many as 305 people. Sampling used purposive sampling method so that 109 people were obtained as samples. The first instrument test and classical assumption test were carried out,nextanalyzed using multiple linear regression analysis, determination, t test and F test.Based on the results of the analysis, it can be said that control, control activities, information and communication have a significant effectt on the efficiency of credit distribution and have no significant effect on the efficiency of credit distribution.